ZABAWA W KONTEKŚCIE KULTUROWYM. CZĘŚĆ I. CZŁOWIEK ZABAWY – OD KOŁYSKI DO WIEKU SĘDZIWEGO - Romanowska, Teresa (Civitas et Lex, 2018)
For centuries people have enjoyed playing. Play is an essential element of everyone’s life, not only children. This article explores own research containing: ethnographic interviews with citizens of Elk region, participant observation of children’s plays and shows by folk artists, survey with preschool and school teachers conducted during traditional play workshops for children. In addition it analyses memories from diaries and from an autobiography. The analysis is supported by examples from literature. Description of some plays gives an opportunity to find out more about everyday life in a particular region in a certain period of time. The literature shows how old are some plays, which are popular and still taught in kindergartens. It is noticed that in the past children, young people and adults had similar plays. Nowadays adults choose mainly dance events, which differ from those described in the article. Children however know and sometimes play the traditional games alongside with new ones. Considering play as a cultural phenomenon it is observed that the rules of children’s plays has not changed, only their form or contents may differ. Children have still enjoyed playing and miming the reality around them.